Evaluating the effects of metformin on irisin and serum biochemical parameters in male sprague-dawley rats fed by a high-fat emulsion diet - Babak Hassan Khan; Parichehreh Yaghmaei; Kazem Parivar; Azadeh Ebrahim Habibi (یافته‌های نوین در علوم زیستی, 2022)
Irisin is a myokine secreted mostly by muscles after exercise, and its secretion level changes in metabolic disorders. The aim of present study was to investigate the effect of metformin on changes in the levels of plasma irisin, blood glucose and insulin resistance in male Sprague-Dawley rats receiving a high-fat emulsion diet. Twenty-four rats were divided into a normal control group (n = 8) and a high-fat diet group (n = 16). Then, high-fat diet group was divided into two subgroups, including high-fat diet control group (n = 8) and metformin group (n = 8). The normal control group received a standard diet. The high-fat diet control group received a high-fat emulsion diet containing corn oil by gavage on a daily basis for six weeks, and the metformin group received a high-fat emulsion diet with metformin (250 mg/kg/daily). At the end of the six-week period, factors such as glucose, insulin, irisin, Adiponectin, insulin resistance, liver enzymes, tumor necrosis factor α (TNF-α), serum lipid profile, lipid profile and lipid peroxidation in liver were measured and PGC-1α gene expression were examined in adipose tissue by Real-time PCR method. Liver histological tests with hematoxylin-eosin staining were performed to evaluate fat accumulation in liver tissue. Blood glucose level, insulin resistance, adiponectin, serum irisin level and liver lipid profile in the group receiving high-fat diet compared to the normal control group increased significantly (P <0. 05). Treatment with metformin caused a significant decrease in the level of these parameters compared to the high-fat diet group (P <0. 05) and an increase in the expression of PGC-1α gene in adipose tissue was observed in this group. As insulin resistance increased in rats receiving the high-fat diet, serum irisin level also increased, and with improving blood glucose and insulin resistance by metformin, serum irisin level was decreased. These results suggested that the elevated irisin levels may be a compensatory response to insulin resistance and impaired glucose metabolism. Hence, irisin could be considered as a potential target for the treatment of type 2 diabetes.